Karakteristik Buah dan Biji Lontar (Borassus Flabelifer L.) - Ite Morina Yostianti Tnunay; Dicky Frengky Hanas; Meri Helsiana Mata (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
The purpose of this study was to provide the data about character of lontar fruit and seeds in Kefamenanu City, North Central Timor Regency. This research was conducted from August to September 2022 using exploration and sample collection methods than contnued with characterization of fruit and seed. The results showed that the lontar fruit and seed in Kefamenanu can be characterized using the characteristics of the diameter of the base of the petals, the diameter of the tip of the petals, the length of the inner petals, the length of the outer petals, the width of the inner petals, the width of the outer petals, the number of petals, color. petals, edges of petals, petal shape, weight of petals, weight of fruit with petals, weight of fruit without petals, fruit diameter, fruit length, fruit circumference, fruit skin color, fruit shape, fruit skin surface, fruit tip and base surface, base color and fruit tip, seed weight, seed length, seed width, seed diameter, endosperm diameter, seed coat thickness, endosperm length, and endoperm color. In conclusion, there are 31 qualitative and quantitative characters that have been used to characterize lontar fruit and seed in Kefamenanu City. Keywords: Fruit and Seed Characters, Lontar